Plasma Etching of SiO2 Using Heptafluoropropyl Methyl Ether and Perfluoropropyl Vinyl Ether. (1st January 2018) - Kim, Jun-Hyun; Park, Jin-Su; Kim, Chang-Koo
Abstract : As alternative to perfluorocompounds, hydrofluoroether and perfluoroalkyl vinyl ether were used for SiO2 etching. SiO2 was etched in heptafluoropropyl methyl ether (HFE-347mcc3)/Ar and perfluoropropyl vinyl ether (PPVE)/Ar plasmas, separately, and their etch characteristics were compared at bias voltages ranging from −400 to −1200 V. The etch rate of SiO2 in a HFE-347mcc3/Ar plasma was approximately 2.5 times higher than that in a PPVE/Ar plasma at a bias voltage of −400 V. However, the difference in the etch rates decreased with increasing bias voltage, reaching nearly zero at a high bias voltage of −1200 V. The change in the etch rate of SiO2 was attributed to not only the amount of F radicals but also the characteristics in the steady-state fluorocarbon films formed on the SiO2 substrate. In the low-bias voltage regime (−400 to −800 V), higher etch rates in a HFE-347mcc3/Ar plasma than those in a PPVE/Ar plasma were obtained because both the thickness and fluorine-to-carbon (F/C) ratio of the steady-state fluorocarbon film controlled the etch rate of SiO2 . On the other hand, the F/C ratio of the steady-state fluorocarbon film, rather than its thickness, limited the etch rate of SiO2 in the high-bias voltage regime (−800 to −1200 V).